1994
DOI: 10.1021/jm00052a015
|View full text |Cite
|
Sign up to set email alerts
|

A Bioactive Fullerene Peptide

Abstract: The highly hydrophobic C60 (buckminsterfullerene) was water solubilized by covalently linking the synthon 1,2-dihydro-1,2-methanofullerene [60]-61-carboxylic acid to the alpha-amino group of the hydrophilic 4-8 sequence of peptide T, known to display potent human monocyte chemotaxis. The resulting compound, characterized by a variety of analytical techniques, including a UV spectrum in aqueous solution, exhibits remarkable chemotactic potency, comparable to that of the parent pentapeptide. Furthermore, this fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
72
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(72 citation statements)
references
References 8 publications
0
72
0
Order By: Relevance
“…Several studies have demonstrated that C60, as a therapeutic antioxidant, works significantly better than other natural and synthetic antioxidants in degenerative diseases (36)(37)(38)(39)(40). It has been reported that carboxyfullerene protects human keratinocytes from apoptosis induced by exposure to oxidative stress (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that C60, as a therapeutic antioxidant, works significantly better than other natural and synthetic antioxidants in degenerative diseases (36)(37)(38)(39)(40). It has been reported that carboxyfullerene protects human keratinocytes from apoptosis induced by exposure to oxidative stress (40).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that fullerene derivatives have some remarkable biologic properties, such as inhibition of the activity of human immunodeficiency virus type 1 (36), promotion of chondrogenesis (37), membranotropic properties, and activation of transmembrane transport of bivalent metal ions (38). In addition, fullerene inhibits neuronal apoptosis by scavenging ROS (39), and protects human skin keratinocytes from ROS-induced cell death after ultraviolet stress (40).…”
mentioning
confidence: 99%
“…Since their discovery [1], unique interactions with biomolecules have been expected and also anticipated from the toxological point of view, because fullerenes have recently been synthesized on a large scale and many researchers have been exposed to them, mainly in the electrochemical field. There are a few interesting studies concerning the biological activities of water-soluble [60]fullerene (C60) derivatives such as DNA-cleaving activity [2] and HIV-1 inhibition activity [3,4]. As for unfunctional fullerenes, owing to their low solubility in water, it is hard to examine the biological activities of fullerenes alone especially in in vitro systems.…”
Section: Introductionmentioning
confidence: 99%
“…In 1985, a third allotrope was discovered and dubbed Buckminsterfullerene because of its geodesic character (1). The preparation of fullerenes in workable quantities led first to applications in chemical and engineering processes and subsequently to the suggested use of fullerenes in biological applications (2)(3)(4) and as templates for the design of experimental pharmaceutical agents, including those with anti-viral (5-9), antioxidant (8)(9)(10)(11)(12), chemotactic (13), and neuroprotective (14) activities.…”
mentioning
confidence: 99%